2017
DOI: 10.1088/1361-648x/aa7efd
|View full text |Cite
|
Sign up to set email alerts
|

On the density of states of circular graphene quantum dots

Abstract: We suggest a simple approach to calculate the local density of states that effectively applies to any structure created by an axially symmetric potential on a continuous graphene sheet such as circular graphene quantum dots or rings. Calculations performed for the graphene quantum dot studied in a recent scanning tunneling microscopy measurement [Gutierrez et al. Nat. Phys. 12, 1069-1075(2016] show an excellent experimental-theoretical agreement.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 24 publications
(123 reference statements)
0
21
0
Order By: Relevance
“…Importantly, both the potentials in eqs.2 and 3 become constant in the two limits of small and large distances, r ≤ r i and r ≥ r f , that would somewhat facilitate the LDOS-computations [20]. In particular case of U g ≡ 0, these potentials U (r) of eqs( 2) and (3) seem to have the ordinary trapezoidal profiles.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Importantly, both the potentials in eqs.2 and 3 become constant in the two limits of small and large distances, r ≤ r i and r ≥ r f , that would somewhat facilitate the LDOS-computations [20]. In particular case of U g ≡ 0, these potentials U (r) of eqs( 2) and (3) seem to have the ordinary trapezoidal profiles.…”
Section: Introductionmentioning
confidence: 96%
“…Given U (r), we computed LDOSs for the studied resonator, using the approach suggested in Refs. [19,20](see Supplementary Materials). Shortly, the computing procedure is as following: (i) solving the Dirac equation of Hamiltonian (1) to calculate LDOSs with a given angular momentum j -the partial LDOSs (S4); (ii) taking the sum of partial LDOSs over all possible j provides LDOS ρ(E, r) (S3) that depends on the energy E and the distance r; and (iii) integrating ρ(E, r) over r provides the total density of states (TDOS) ρ T (E) (S9).…”
Section: Introductionmentioning
confidence: 99%
“…The principle signature of bound or quasi‐bound states in Dirac materials is through the local density of states data obtained by STM measurements . As mentioned previously, the results of the atomic cluster experiments of ref.…”
Section: Experimental Signatures Of Confinementmentioning
confidence: 96%
“…Around Dirac points electrons exhibit Klein tunneling which makes it difficult to control electrons using external fields in pristine graphene [2]. However, it has been theoretically shown that it may still be possible to create quasibound states (QBS) using external electric fields [3][4][5][6]. Magnetic fields combined with electric fields were also shown to produce confinement in pristine graphene [7][8][9][10].…”
mentioning
confidence: 99%
“…( 2), the eigenstates of H K (K ) [Eq. ( 1)] of energy E , and the total angular momentum quantum number j = m ± 1/2 around K (K ) Dirac points, are given as follows [4][5][6]:…”
mentioning
confidence: 99%